Blind Buying Intention of Local Perfumes: An Indonesian Consumer Perspective - Argyanti, Talitha; Hussein, Ananda Sabil; Oktaviani, Fitri Hariana (Universitas Brawijaya, 2025)
Perfume was one of the most sold products online in Indonesia and was predicted to continue growing each year. However, Indonesian consumers still tended to choose perfumes from long-established local and international brands available in offline stores. As a result, emerging local perfume brands that primarily focused on online sales faced great challenges in winning the competition. As a sensorial-based product with a high level of uncertainty, perfume was difficult to evaluate in online purchases since consumers could not try it beforehand. Using the Uncertainty Reduction Theory construct, this study examined how product descriptions, online reviews, and interactions with the seller influenced the blind buying intention of local perfumes online in Indonesia. This study used an explanatory quantitative approach with a survey method. A total of 306 respondents who had previously purchased local perfume online without trying it first were selected through purposive sampling. The results of multiple linear regression analysis indicated that product descriptions, online reviews, and interactions with the seller affected the intention to blind buy local perfumes online.